Modeling and simulation of stator and rotor faults of induction motor and their experimental comparison - Dwivedi, Sanjeet Kumar; Dannehl, J. (IEEE, 2017)
© 2017 IEEE. This paper presents a comprehensive research study on the nature of selected stator and rotor fault of Induction Motor. In this article a mathematical model and a Matlab/ Simulink based simulation model is developed and simulation results for stator and rotor faults of induction motors are presented. Experimental evaluation of harmonics and negative sequence component (measure of unbalance) of stator winding current is obtained in both healthy and faulty condition of Induction motor. The simulation and experimental results show close agreements between them. This developed mathematical model and simulation model is important to understand physics of fault phenomenon in Induction motor and to generate required data to develop reliable fault detection algorithms for Induction Motor.